MONITORING KARBON MONOKSIDA (CO) DAN PARAMETER METEOROLOGIS DI TERMINAL TAWANG ALUN KABUPATEN JEMBER - Norry Levi Purnama; Yushardi Yushardi; Agus Abdul Gani (FKIP Universitas Jember, 2018)
AbstractTawang Alun Terminal Jember Regency is one of the dense areas ofvehicles have potential to experience carbon monoxide gas pollution and very lowrainfall compared to the surrounding neighborhoods. This research has shown thecondition of air and carbon monoxide concentration in terminal area of TawangAlun. Monitoring used a set of sensor-based tools with an Arduino microcontroller.The results of monitoring of carbon monoxide and meteorological parameters,obtained the highest concentration of carbon monoxide occured during the day butgradually decreased in the afternoon until late in the night when the temperaturewas getting down and the air humidity increases. In contrast to the amount of windspeed that showed the linear distribution pattern as time changed. The averageresult of carbon monoxide measurements on holidays is 71,000-158,000 μg / Nm3 onweekdays of 62,000-69,000 μg /Nm3. This value showed that has exceeded theambient air quality standard limit for carbon monoxide gas is 30,000 μg / Nm3. Theamount of carbon monoxide content is influenced by the volume of vehicles with aregression rate of 82.3%..Keywords: Carbon Monoxide, meteorological parameters, the ambient air qualitystandard